USING THE CIDEPE CHART AS A TEACHING TOOL FOR LEARNING TRIGONOMETRY - Belonsi, Marcelo Henrique; da Cunha, Maria Francisca; de Lima, Luciano Feliciano; da Costa, Rogerio Ferreira; Junqueira, Manoel Moraes (Seven Editora, 2026)
The research was motivated by the need to overcome traditional and fragmented teaching of trigonometry, which prioritizes algebraic and static geometric approaches, hindering students' conceptual understanding. The main objective was to promote a more dynamic and intuitive learning process by employing the CIDEPE Board as a didactic tool, combined with historical contextualization and active student participation. The methodology was based on explanatory research and action research, using quantitative and qualitative questionnaires, as well as group activities with the didactic material, which represents the trigonometric cycle with a movable diameter. The results indicated a high level of student satisfaction, particularly regarding positive self-perception of learning and the deepening of essential details, such as determining quadrants. It is concluded that the success of the proposal is due not only to the material resource but also to the historical and interactive teaching approach, corroborating previous research in the field.